2015
DOI: 10.1111/ele.12424
|View full text |Cite
|
Sign up to set email alerts
|

Abundance of common species, not species richness, drives delivery of a real‐world ecosystem service

Abstract: Biodiversity-ecosystem functioning experiments have established that species richness and composition are both important determinants of ecosystem function in an experimental context. Determining whether this result holds for real-world ecosystem services has remained elusive, however, largely due to the lack of analytical methods appropriate for large-scale, associational data. Here, we use a novel analytical approach, the Price equation, to partition the contribution to ecosystem services made by species ric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

28
524
3
9

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 534 publications
(564 citation statements)
references
References 49 publications
28
524
3
9
Order By: Relevance
“…Our findings may apply directly to herbivorous marine zooplankton [14] and to herbivorous terrestrial insects [30], in which the impact of key traits on the biomass of lower trophic levels has been recently demonstrated. Additionally, our results may also be representative of other ecosystem functions, such as pollination, in which competitive asymmetry plays a larger role than complementarity [10]. The experimental approach we used, separating the role of a key functional trait and phylogenetic distances, provides exciting and promising avenues to understand how evolutionary convergences and divergences affect trophic interactions and shape ecosystem functioning.…”
Section: Discussionmentioning
confidence: 90%
“…Our findings may apply directly to herbivorous marine zooplankton [14] and to herbivorous terrestrial insects [30], in which the impact of key traits on the biomass of lower trophic levels has been recently demonstrated. Additionally, our results may also be representative of other ecosystem functions, such as pollination, in which competitive asymmetry plays a larger role than complementarity [10]. The experimental approach we used, separating the role of a key functional trait and phylogenetic distances, provides exciting and promising avenues to understand how evolutionary convergences and divergences affect trophic interactions and shape ecosystem functioning.…”
Section: Discussionmentioning
confidence: 90%
“…For amphibian skin bacterial communities, however, we found that most of the highly prevalent and dominant bacterial phyla, families, and OTUs were cultured. This is encouraging, because these are the bacteria whose functions we are interested in, as dominant community members are often functionally important (70). In grassland ecosystems, for example, dominant grass species play an important role in community productivity and resistance to invasion (71,72).…”
Section: Discussionmentioning
confidence: 99%
“…However, there is a danger that current 68 regional and local assessments of ecosystem functions and management advice do not 69 incorporate such risk assessments. This could result in poor management advice and 70 undervaluation of the importance of biodiversity, because whilst relatively low levels of 71 biodiversity can be adequate to provide current function [12], higher levels might be needed 72 to support similar levels of function under environmental change [2,[13][14][15][16][17][18]. Therefore, 73 there is a need to identify the characteristics of resilient ecosystem functions and capture 74 these in both predictive models and management guidance.…”
mentioning
confidence: 99%